Estrogen differentially regulates transcriptional landscapes of preoptic and arcuate kisspeptin neuron populations - Göcz, Balázs; Takács, Szabolcs; Skrapits, Katalin; Rumpler, Éva; Solymosi, Norbert; Póliska, Szilárd; Colledge, William H.; Hrabovszky, Erik; Sárvári, Miklós (Frontiers in Endocrinology, 2022)
Kisspeptin neurons residing in the anteroventral periventricular nucleus (KPAVPV) and the arcuate nucleus (KPARC) mediate positive and negative estrogen feedback, respectively. Here, we aim to compare transcriptional responses of KPAVPV and KPARC neurons to estrogen. Transgenic mice were ovariectomized and supplemented with either 17β-estradiol (E2) or vehicle. Fluorescently tagged KPAVPV neurons collected by laser-capture microdissection were subjected to RNA-seq. Bioinformatics identified 222 E2-dependent genes. Four genes encoding neuropeptide precursors (Nmb, Kiss1, Nts, Penk) were robustly, and Cartpt was subsignificantly upregulated, suggesting putative contribution of multiple neuropeptides to estrogen feedback mechanisms. Using overrepresentation analysis, the most affected KEGG pathways were neuroactive ligand-receptor interaction and dopaminergic synapse. Next, we re-analyzed our previously obtained KPARC neuron RNA-seq data from the same animals using identical bioinformatic criteria. The identified 1583 E2-induced changes included suppression of many neuropeptide precursors, granins, protein processing enzymes, and other genes related to the secretory pathway. In addition to distinct regulatory responses, KPAVPV and KPARC neurons exhibited sixty-two common changes in genes encoding three hormone receptors (Ghsr, Pgr, Npr2), GAD-65 (Gad2), calmodulin and its regulator (Calm1, Pcp4), among others. Thirty-four oppositely regulated genes (Kiss1, Vgf, Chrna7, Tmem35a) were also identified. The strikingly different transcriptional responses in the two neuron populations prompted us to explore the mechanism further. We identified twelve and seventy E2-dependent transcription factors in KPAVPV and KPARC neurons, respectively. While none of the twelve interacted with estrogen receptor-α, eight of the seventy did. We propose that an intricate, multi-layered transcriptional mechanism exists in KPARC neurons and a less complex one in KPAVPV neurons. These results shed new light on the complexity of estrogen-dependent mechanisms acting in the two functionally distinct kisspeptin neuron populations and implicate additional neuropeptides and mechanisms in estrogen feedback.